BEERS CRITERIA: AN UP-TO-DATE TOOL FOR DETECTING INAPPROPRIATE PRESCRIPTION IN ELDERLY - Stojanović, Marko (Medical Research, 2024)
Potentially inappropriate medications (PIM) are drugs that can cause significant unnecessary harm to patients. Prescribing PIM can cause significant healthcare problems, especially if there is a safer, similar, or even more effective alternative for treatment. They are the cause of significant health issues that lead to increased treatment costs and a reduction in life quality. The main problem with the treatment of the geriatric population is the missing of specific guidelines for treatment. This is mainly because the clinical trials which are the main pillar of clinical guidelines are usually acquiring people aged 18 to 65, leaving the geriatric population aside. For this reason, and to reduce the PIMs prescription in the geriatric population many guidelines were created among which the AGS Beers criteria were the first and still are the leading and most comprehensive tool for this purpose. Since 1991 Beers criteria have gone through several updates and changes in format, and since 2012 they came under the control of the American Geriatric Society. The constant updates and work on these guidelines kept these guidelines on top of the other guidelines in this field. Considering all of these it is imperative for every clinician that works with geriatric patients to know these guidelines and to utilize them properly as explained in these criteria.